The Grand Canal at Versailles: Geotechnical investigation, II - Vernhes, J.D.; Saulet, P.; Heitzmann, A. (Geotechnical Engineering for the Preservation of Monuments and Historic Sites III, 2022)
The park of the Palace of Versailles required major geotechnical developments whose center-piece is called the Grand Canal, designed by André Le Nôtre and dug in the 1670s on behalf of King Louis XIV. This exceptional work was the subject of an archival study, the main results of which were communicated on the occasion of the ECSMGE in Reykjavik in September 2019. The article proposed for the 3rd TC301 International Symposium reports on the in situ investigations and numerical field models carried out, with UniLaSalle students, over a period of two years, allowing in principle to answer questions that remained unaddressed. The construction of the current relief map and of the supposed relief map before work makes it possible to estimate a volume of excavated material and embankments of nearly 700,000 m3 and 500,000 m3 respectively, realistic orders of magnitude. The apparent unbalance has no justification other than the current uncertainties in topographic models. The question of the canal watertightness and its hydraulic relationship to the surrounding ground, given the available field data, paradoxically appears less clear today than in the conclusions of the previous article. The real nature of the basin deposit, apparently colluvial to significant depths, complicates attempts to interpret both Le Nôtre's project and the current functioning of his work. The park of the Palace of Versailles required major geotechnical developments whose center-piece is called the Grand Canal, designed by André Le Nôtre and dug in the 1670s on behalf of King Louis XIV. The apparent unbalance has no justification other than the current uncertainties in topographic models. The question of the canal watertightness and its hydraulic relationship to the surrounding ground, given the available field data, paradoxically appears less clear today than in the conclusions of the previous article. The real nature of the basin deposit, apparently colluvial to significant depths, complicates attempts to interpret both Le Nôtre's project and the current functioning of his work. An important aspect of these results for further earthworks analysis is that a coherent scenario of land movement should take into account this phasing: the balance of movements at the end of a phase should be in equilibrium.